Two c's in a pod: cosmology-independent measurement of the Type Ia supernova colour–luminosity relation with a sibling pair. Issue 4 (14th October 2021) - Biswas, Rahul; Goobar, Ariel; Dhawan, Suhail; Schulze, Steve; Johansson, Joel; Bellm, Eric C; Dekany, Richard; Drake, Andrew J; Duev, Dmitry A; Fremling, Christoffer; Graham, Matthew; Kim, Young-Lo; et al.
ABSTRACT: Using Zwicky Transient Facility (ZTF) observations, we identify a pair of 'sibling' Type Ia supernovae (SNe Ia), i.e. hosted by the same galaxy at z = 0.0541. They exploded within 200 d from each other at a separation of 0.6 arcsec corresponding to a projected distance of only 0.6 kpc. Performing salt2 light-curve fits to the gri ZTF photometry, we show that for these equally distant 'standardizable candles', there is a difference of 2 mag in their rest-frame B -band peaks, and the fainter supernova (SN) has a significantly red salt2 colour c = 0.57 ± 0.04, while the stretch values x 1 of the two SNe are similar, suggesting that the fainter SN is attenuated by dust in the interstellar medium of the host galaxy. We use these measurements to infer the salt2 colour standardization parameter, β = 3.5 ± 0.3, independent of the underlying cosmology and Malmquist bias. Assuming the colour excess is entirely due to dust, the result differs by 2σ from the average Milky Way total-to-selective extinction ratio, but is in good agreement with the colour–brightness corrections empirically derived from the most recent SN Ia Hubble–Lemaitre diagram fits. Thus we suggest that SN 'siblings', which will increasingly be discovered in the coming years, can be used to probe the validity of the colour and light-curve shape corrections using in SN Ia cosmology while avoiding important systematic effects in their inference from global multiparameter fits to inhomogeneous data sets, and also help constrain the role of interstellar dust in SN Ia cosmology.